2019
DOI: 10.1093/ajcp/aqz164
|View full text |Cite
|
Sign up to set email alerts
|

Rapid On-Site Evaluation With Telecytology Significantly Reduced Unsatisfactory Rates of Thyroid Fine-Needle Aspiration

Abstract: Objectives We evaluated telecytology rapid on-site evaluation (ROSE) for thyroid ultrasound-guided fine-needle aspiration. To the best of our knowledge, this study is the first case-control clinical trial of thyroid telecytology. Methods We introduced on-site ROSE in our institution’s thyroid clinic for 6 months, followed by telecytology for 12 months. Our institution’s ultrasound clinic, where ROSE is not provided, was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…Despite that some might argue that ROSE benefits may outweigh costs by decreasing the number of FNA repeats [21]. Other institutes implemented tele cytopathology for suspicious nodules to overcome shortage of onsite cytopathologist with relatively good results, however with increased cost and procedure time [13,22].…”
Section: Discussionmentioning
confidence: 99%
“…Despite that some might argue that ROSE benefits may outweigh costs by decreasing the number of FNA repeats [21]. Other institutes implemented tele cytopathology for suspicious nodules to overcome shortage of onsite cytopathologist with relatively good results, however with increased cost and procedure time [13,22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that telecytology for ROSE is cost-effective, has high concordance with traditional (ie, pathologist physically present on-site) ROSE and final diagnosis, and with current advances in technology and internet or Wi-Fi connectivity is relatively easy to implement. [11][12][13][14][15][16][17] However, an American Society of Cytopathology survey in 2019 showed that only 21.9% of participating practices utilised telecytology for ROSE despite the fact that ROSE service was provided by 95.4% of the 541 respondents. 18 The survey also demonstrated that the practice patterns for ROSE vary considerably and that unfortunately there are no recommended guidelines yet for the implementation and quality assurance of ROSE in different clinical settings.…”
Section: Discussionmentioning
confidence: 99%
“…A medida que aumenta la cantidad de procedimientos mínimamente invasivos, también aumenta la cantidad de sitios que requieren ROSE, y, a su vez, un número mayor de personal con conocimiento de citología en las instituciones. La telecitología representa una solución razonable para aumentar la eficiencia del personal y permite al patólogo permanecer en el laboratorio, mientras un citotecnólogo envía las imágenes desde el lugar donde se está realizando el procedimiento [48]. La aparición de tecnologías de imágenes digitales rápidas y de alta resolución, ha hecho posible la telecitología y ha permitido hacer más eficiente el proceso [49].…”
Section: Telecitología Y Roseunclassified